The prediction of crack propagation in coarse grain RR1000 using a unified modelling approach. (August 2020) - Engel, B.; Rouse, J.P.; Hyde, C.J.; Lavie, W.; Leidermark, D.; Stekovic, S.; Williams, S.J.; Pattison, S.J.; Grant, B.; Whittaker, M.T.; Jones, J.P.; Lancaster, R.J.; et al.
Highlights: In-phase and out-of-phase TMF tests can be predicted with good accordance to experimental results using a unified formulation, based on material parameters deducted from isothermal crack growth test. Because of the strong sensitivity of the crack growth to the microstructure during IP testing, a precipitation size dependent parameter S was introduced. It has been shown that the crack growth rate increases with a decreasing size as well as amount of tertiary γ'. This can be attributed to increased plastic deformation in the area of the crack tip, caused by a decrease of critical resolved shear stress for weakly coupled dislocation to shear the particles. OP TMF tests show no sensitivity to microstructural aspects. Since peak load is reached at minimum temperature, plastic deformation primarily occurs in the γ matrix, due to high stiffness differences to the γ' particles. Therefore no modification of the crack growth rates using S are necessary. Abstract: The polycrystalline nickel-base superalloy RR1000 is used as turbine rotor material in Rolls-Royce aero engines and has to withstand a wide variety of load and temperature changes during operation. In order to maximize the potential of the material and to improve component design, it is of great interest to understand, and subsequently be able to accurately model the crack propagation caused by thermo-mechanical fatigue conditions. In this work, experimental data is analysed and used to inform unified modelling approaches in order to predict the crack propagation behaviour of RR1000 under a variety of stress-controlled thermo-mechanical fatigue conditions.